Strain engineering in 2D hBN and graphene with evaporated thin film stressors - Azizimanesh, Ahmad; Dey, Aditya; Chowdhury, Shoieb A.; Wenner, Eric; Hou, Wenhui; Peña, Tara; Askari, Hesam; Wu, Stephen M. (Applied physics letters, 2023)
We demonstrate a technique to strain two-dimensional hexagonal boron nitride (hBN) and graphene by depositing stressed thin films to encapsulate exfoliated flakes. We choose optically transparent stressors to be able to analyze strain in 2D flakes through Raman spectroscopy. Combining thickness-dependent analyses of Raman peak shifts with atomistic simulations of hBN and graphene, we can explore layer-by-layer strain transfer in these materials. hBN and graphene show strain transfer into the top four and two layers of multilayer flakes, respectively. hBN has been widely used as a protective capping layer for other 2D materials, while graphene has been used as a top gate layer in various applications. Findings of this work suggest that straining 2D heterostructures with evaporated stressed thin films through the hBN capping layer or graphene top contact is possible since strain is not limited to a single layer.